Potential‐Dependent Kinetics and Reaction Pathways of Low‐Potential Furfural Electrooxidation with Anodic H2 Production - Zhaohui Wu; Guihao Liu; Ziheng Song; Yihang Hu; Tianqi Nie; Yu‐Fei Song (Small Science)
The low‐potential furfural electrooxidation reaction (FFOR) on copper‐based catalysts provides a novel pathway to upgrade biomass and produce H2 simultaneously on anode. Herein, a series of oxide‐derived copper catalysts (OD‐Cu‐x, x represents electroreduction time) with distinct Cu0/Cu+ ratios and residual content of lattice oxygen are successfully constructed by tuning in‐situ electroreduction time. When applied for FFOR, the OD‐Cu‐600 with a Cu0/Cu+ ratio of 83.3% shows the Faradaic efficiency of 96.1% for furoic acid (FA) and 97.4% for H2, which can be achieved at a lowest potential of 0.081 V versus RHE at 10 mA cm−2 in continuous 10 cycles, outperforming the state‐of‐art Cu‐based catalysts reported so far. Detailed characterization and density functional theory (DFT) calculations prove that the moderate coverage (25% based on DFT models) of Cu(OH)ads surface species generated by Cu+ during the electrooxidation process endows the optimal furfural molecule adsorption and activation. Moreover, this potential‐dependent coverage of surface OH can promote the kinetics of *H transfer to the Cu surface, allowing the H2 evolution from the anode. The Cu0/Cu+ ratio (83.8%) and suitable applied potential windows (0 to 0.4 V vs RHE) are both responsible for the co‐production of FA and H2 with high intrinsic activity and efficient H atom utilization.